2007
DOI: 10.1016/j.compstruct.2006.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory effect and mechanical properties of carbon nanotube/shape memory polymer nanocomposites

Abstract: Abstract:Carbon nanotubes (CNT) have remarkable mechanical properties with very high elastic modulus and electrical conductivity. Shape memory polymer (SMP) as one of smart materials is characterized with its remarkable recoverability and shape memory effect, but its mechanical properties such as strength and elastic modulus is not high enough. In this study, CNT/SMP nanocomposites were developed with the typical CNTs of the vapor growth carbon fibers (VGCFs). A fine and homogeneous dispersion of VGCF througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(112 citation statements)
references
References 36 publications
3
109
0
Order By: Relevance
“…Gall et al [22] prepared and characterized SiC/epoxy composite and found that the recoverability of the composite was perfect for SiC weight fractions below 40%. Ni et al [23] prepared CNT/ polyesterpolyol SMP nanocomposite. They found that the recovery stress of CNT/polyesterpolyol with 3.3% weight fraction of CNTs will reach almost twice of that in bulk SMP.…”
Section: Introductionmentioning
confidence: 99%
“…Gall et al [22] prepared and characterized SiC/epoxy composite and found that the recoverability of the composite was perfect for SiC weight fractions below 40%. Ni et al [23] prepared CNT/ polyesterpolyol SMP nanocomposite. They found that the recovery stress of CNT/polyesterpolyol with 3.3% weight fraction of CNTs will reach almost twice of that in bulk SMP.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be attributed to the addition of emulsifiers acting as a plasticizer in the preparation of the water-borne epoxy resin. However, the yield strength of the pristine epoxy resin is twice as higher as that of SM polyurethanes at 25 1C [11,12].…”
Section: Resultsmentioning
confidence: 95%
“…Ni 18 gives the relationships between composite Young's modulus of CNT/SMP and CNTs weight fracton of the vapor growth carbon fibers (VGCFs). With the increasing of VGCFs the Young's modulus increased rapidly in temperature 25°.…”
Section: Buckling Of Cnt/smp Composite Shellmentioning
confidence: 99%